INFLUENCING FACTORS OF RESIDENTS’ PARTICIPATION IN THE SELF - RENOVATION BEHAVIOR OF DANGEROUS AND OLD RESIDENTIAL AREAS BASED ON THE THEORY OF PLANNED BEHAVIOR - Yi Shi (PEOPLE: International Journal of Social Sciences, 2026)
This study investigates the determinants and pathways of residents’ intention to participate in owner-led Self - Renovation in Dangerous and Old Residential Areas, using Haikou, China as the empirical context. Grounded in the Theory of Planned Behavior (TPB) and informed by the theory of the production of space, the research builds an integrated framework that links renewal-information perceptions (policy perception, planning/design perception, and perceived community management capacity), spatial conditions (basic living conditions, public activity space, and infrastructure), and community relations (community cohesion, sense of community belonging, and social support) to TPB components (behavioral attitude, subjective norms, and perceived behavioral control), and ultimately to participation intention. Data were collected through door-to-door and on-site surveys in 12 designated districts, yielding 343 valid homeowner responses. Reliability and validity tests indicate satisfactory measurement quality, and structural equation modeling shows good overall model fit. Results confirm that attitude, subjective norms, and perceived behavioral control significantly and positively predict participation intention, with subjective norms exerting the strongest effect. Policy, planning/design, and community management perceptions significantly enhance both attitude and subjective norms. Poorer perceived living conditions, insufficient public space, and inadequate infrastructure strengthen positive attitudes toward participation. Community cohesion, belonging, and social support reinforce attitude and subjective norms, while belonging and social support also increase perceived behavioral control. The findings provide targeted leverage points for designing communication, mobilization, and support strategies to promote resident participation in urban self-governance renewal.